2016
DOI: 10.1155/2016/7682917
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pigmented Basal Cell Carcinoma with 3 mm Surgical Margin in Asians

Abstract: Background. In Asians, most basal cell carcinomas (BCCs) are pigmented with clear borders. The consensus of 4 mm surgical margin for BCC largely depends on studies in nonpigmented BCCs in Caucasians. However, little is known about recurrences of pigmented BCCs with a narrower surgical margin. We aimed to investigate 5-year recurrence of BCCs, either pigmented or nonpigmented, in Taiwanese with 3 mm surgical margin. Materials and Methods. 143 patients with BCC (M/F = 66/77, average 64 years) were confirmed path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…They used a 5-year follow-up design to determine whether a 3 mm surgical margin was appropriate for excision of pigmented and non-pigmented BCC, and they used recurrence as the outcome measurement. They concluded that a 3 mm margin is adequate for excision of pigmented BCC, but non-pigmented BCC had a higher risk of recurrence and thus needs careful follow up [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…They used a 5-year follow-up design to determine whether a 3 mm surgical margin was appropriate for excision of pigmented and non-pigmented BCC, and they used recurrence as the outcome measurement. They concluded that a 3 mm margin is adequate for excision of pigmented BCC, but non-pigmented BCC had a higher risk of recurrence and thus needs careful follow up [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…7 However, only one patient (0.95%) showed local recurrence during a 5-year follow-up. 7 Nakamura et al investigated the appropriate surgical margins in 120 Japanese BCC patients. 16 They reported that complete excision was achieved in 51 low-risk BCC cases regardless of margin width.…”
Section: Discussionmentioning
confidence: 94%
“…In a cohort of Japanese patients with BCC, Takenouchi et al 6 reported that the 5-and 10-year recurrence rates after complete excision without use of MMS were 0.4% and 0.8%, respectively. Further, in a group of Taiwanese patients with BCC, Lin et al 7 reported a 5-year local recurrence rate of 2.3% even in a group with close margins (within 1 mm). Therefore, the use of MMS is very limited in Japan and few institutions have the equipment and trained technicians for performing MMS.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations